Instructional Learning Model on WhatsApp Media Problem in a Pandemic Covid-19 Period - Mohammad Imam Sufiyanto; Rocyhan Yasin; Hesty Kusumawati (IAIN Palopo, 2021)
The purpose of this research is to find out the influence of learning (Problem Based Instruction) on learners at the elementary unit level (elementary school) in one of the schools located in the Pamekasan area. This study is qualitative descriptive, the study subjects are elementary school students as many as 150 students consisting of 78 men and 72 women. Techniques in this study use interviews and questionnaires. Research instruments are with concessioners, as well as data analysis techniques by sampling methods. The results of this study were from 150 students who joined three classes in each class containing 50 people in WhatsApp groups. Known on the interpretation scale is 336 ≤ 307 < 400 which is categorized very well done during the covid-19 pandemic online with WhatsApp from media. This study concludes that the PBI learning model is very suitable to be done at the elementary unit level or elementary school with social media platforms that are WhatsApp connected to their respective class groups (WAG). Keywords: